Leader-Member Exchange and Job Satisfaction - Durarajen, Amararajan (2004)
Leader-member exchange (LMX) theory examines the relationship and role processes between a leader and individual followers. The theory is based on the understanding that leaders establish individual and mutually exchanged relationships with those in a subordination position. A leader typically has one major prevailing style of leadership, but most do not treat all followers the same way (Thomas, 2003)